Market-economic experiments in China's planned economy - Wolfgang Klenner (Intereconomics, 1981)
Aware of the limitations of central economic planning, the Chinese leaders have issued instructions to complement the economic order, at least on an experimental scale, by elements of the market economy. The author attended the deliberations on the new Ten-Year Plan last autumn, and here he draws a picture of the intentions underlying the reform proposals and the problems likely to arise.
Keywords: 330